南洋大学的南洋研究（1956-1980) = "Nanyang studies" in Nanyang University (1956-1980) - 高建东 Loh, Choy Mun (2011)
本文主要探讨的是南洋大学（以下简称“南大”）从事南洋研究的过程及其南洋研究成果。前者包括开设课程、教学与研究、设立研究机构等活动；后者则主要是南大师生的作品和研究著作。本文的研究范畴是以史地为核心的南洋研究在南大的发展和规模。本文的研究时限划在1956年南大史地系开课起至1980年南大与新大合并为止。 This thesis investigates the research process as well as the research outcomes of “Nanyang Studies” in Nanyang University. The former includes the setting up of courses, teaching and research, the establishment of research institutions and other activities; the latter refers mainly to the works and publications of teachers and students. The study covers the development and scale of “Nanyang Studies”, a field of research in Nanyang University centering on history and geography. The period under study is between 1956 to 1980, from the commencement of classes at the Departments of History and Geography in Nanyang University to the merger of Nanyang University and the University of Singapore.